Rethinking customer engagement design: Using customer-mobilized engagement (CME) to grow business networks - Davey, J.; O'Brien, I.; Ouschan, Robyn; Parkinson, J. (ELSEVIER SCIENCE INC, 2022)
The purpose of this paper is to propose a conceptual framework of customer-mobilized engagement (CME) pathways where customers actively identify, engage, and mobilize hidden (new) actors (and their resources) who are beyond the reach of the focal organization. As a large proportion of value stems from connections with multiple business networks, an organization's customer network becomes an important strategic asset contributing to competitive advantage and survival. Taking a propositional approach, we conceptualize the CME pathway and elaborate on factors critical to CME drawing on two organizations for illustrative purposes. We develop three propositions explaining how customer-mobilized engagement of hidden (new) actors, resources, and engagement platforms connect dynamically via the mobilizing customer. The reinterpreted communicative value proposition increases the contribution of hidden actors and enhances and expands value outcomes for actors within the CME pathway including increased sustainable competitive advantage for the focal organization. Adopting CME adds new resources, in different ways to deliver value to an organization's diverse business streams and grow their business networks. The CME pathway provides industrial marketing managers with an agile tool to guide the design of their offerings which can adapt across business contexts and time as the social, economic, political and technological environment changes.